SERCA plays a crucial role in the toxicity of a betulinic acid derivative with potential antimalarial activity. (1st May 2018) - Diedrich, Denise; Wildner, Andreia C.; Silveira, Thayse F.; Silva, Gloria N.S.; Santos, Francine dos; da Silva, Elenilson F.; do Canto, Vanessa P.; Visioli, Fernanda; Gosmann, Grace; Bergold, Ana M.; Zimmer, Aline R.; Netz, Paulo A.; et al.
Abstract: Malaria is one of the most significant infectious diseases that affect poor populations in tropical areas throughout the world. Plants have been shown to be a good source for the development of new antimalarial chemotherapeutic agents, as shown for the discovery of quinine and artemisinin derivatives. Our research group has been working with semisynthetic triterpene derivatives that show potential antimalarial activity toward different strains of Plasmodium falciparum by specifically modulating calcium pathways in the parasite. Promising results were obtained for nanomolar concentrations of the semisynthetic betulinic acid derivative LAFIS13 against the P. falciparum 3D7 strain in vitro, with a selectivity index of 18 compared to a mammalian cell line. Continuing these studies, we present here in vitro and in vivo toxicological evaluations of this compound, followed by docking studies with PfATP6, a sarco/endoplasmic reticulum Ca +2 -ATPase (SERCA) protein. LAFIS13 showed an LD50 between 300 and 50 mg/kg, and the acute administration of 50 mg/kg (i.p.) had no negative effects on hematological, biochemical and histopathological parameters. Based on the results of the in vitro assays, LAFIS13 not exerted significant effects on coagulation parameters of human peripheral blood, but a hemolytic activity was verified at higher concentrations. According to the molecular docking study, the PfATP6 protein may be a target for LAFIS13, which corroborates its previously reported modulatory effects on calcium homeostasis in the parasite. Notably, LAFIS13 showed a higher selectivity for the mammalian SERCA protein than for PfATP6, thus impairing the selectivity between parasite and host. In summary, the direct interaction with calcium pumps and the hemolytic potential of the compound proved to be plausible mechanism of LAFIS13 toxicity. Graphical abstract: Highlights: Effects in peripheral blood in vitro . In vivo acute toxicity. In silico approach to ilicit tocixity